1978
DOI: 10.1002/mrc.1270111203
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 chemical shifts of some model carboxylic acids and esters

Abstract: Selected model carboxylic aads and esters dissolved in deuteriochloroform have been studied by carbon-13 nuclear magnetic resonance under standardized conditions. Assignments of the chemical shifts have been made for all samples, and the spin-lattice relaxation times and nuclear Overhauser effects measured for a few selected esters. The results are intended to provide a practical aid for the analysis of carboxylic acids and esters of a more complex nature (e.g. polymers, natural products, etc.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(15 citation statements)
references
References 3 publications
3
10
0
2
Order By: Relevance
“…For the s-cis rotamers of a few members of this series such chemical shifts were reported by Couperus et al 18 The present results are in fair agreement with those values once the di †erent refer- …”
Section: Resultssupporting
confidence: 94%
“…For the s-cis rotamers of a few members of this series such chemical shifts were reported by Couperus et al 18 The present results are in fair agreement with those values once the di †erent refer- …”
Section: Resultssupporting
confidence: 94%
“…Six azelaoyl peaks with distinct chemical shifts and Figure 2 for labeling) since carbons 2 and 8 should be at the typical 13 C chemical shift region of covalently bound carbons to carbonyls from 34 to 48 ppm. 79 The peak labeled with f below 33.7 ppm is assigned to carbon 8 of the azelaoyl chain since we expect the remaining carbon 2 to have a similar chemical shift (close to 33.9) to the carbons 2 and 2′ of the POPC sn-1 and sn-2 chains, respectively. The high spectral resolution achieved allowed us to accurately determine the order parameters for all azelaoyl peaks except for the ones labeled a and f with order parameters too small for an accurate determination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Comparison of the I3C nrnr spectra of the three compounds 1, 2, and 12 indicated that the free carboxyl group of B (6c 183.5) is associated with the downfield carboxymethyl group 176.4) of the dimethyl ester 2. It is therefore assigned as the C-21 carboxyl group on the basis of normal I3C substitution rules (5). Thus compound B is 3,4-secotirucalla-4(28),7,24-trien-3,21-dioic acid 3-methyl ester 12.…”
mentioning
confidence: 99%